Effect of Education on the Attitudes of Pregnant Women in Ante Natal Care for Stunting Prevention in Talang Jerinjing Village, Indragiri Hulu Regency - Yulianto, Yulianto; Deswita, Deswita; Kurniadi, Rizki; Thomas, David P. (Adi Husada Nursing Journal, 2024)
Talang Jerinjing Village is a target zone in endeavors to progress family sustenance since the foundation of the people in this zone could be a primitive tribal society with a high level of instruction. Hindering can be anticipated by keeping up the well-being and sustenance of pregnant women from an early age since a baby's development starts within the womb. The positive behavior of moms to avoid hindering amid pregnancy is the most thing. This inquiry points to distinguish the impact of instruction on the states of mind of pregnant ladies in antenatal care to avoid hindering in Talang Jerinjing Village, Indragiri Hulu area. The research method was a quasi-experiment by assessing the perspectives of 20 pregnant women before and after education about the importance of ante-natal care and preventing stunting. The variables in this study are health education and attitudes of pregnant women in ante-natal care to prevent stunting. The instrument used was a questionnaire. This research shows a significant change in the attitudes of pregnant women before and after school with p<0.05. Based on these results, it can be seen that health education influences changes in the attitudes of pregnant women in efforts to prevent stunting. Increasing pregnant women's understanding of stunting and efforts to prevent stunting during pregnancy can increase awareness and motivate mothers to try to avoid stunting during pregnancy.